Age-Associated Changes in Dog Synovial Membrane Fibres, Capillaries and Nerves - Sagiroglu, Ayse Oya (Medwell Online, 2012)
Age related changes in the fibres, capillaries and nerves in the synovial membrane of the 24 (12 male and 12 female) Kangal hybrid-breed dogs were studied. The ages of the dogs varied and were classified in. 3 groups; young (0-3 months), middle aged (3.5-6 months) and old (7 months to 6 years old). Synovial intimal layers were made of 1-2 layered intimal cells in the young group dogs and increased up from 3-5 to 2-6 multi-layered cells in the middle aged and the old dogs. The subintimas of young and middle aged groups were in areolar, adipose and areola-adipose types and were in fibrous type in the old group dogs. The collagen fibres of young group dogs were rare and scattered and they increased and occurred as bands and bundles in the synovium of the middle aged and old group dogs. The collagen fibres around the capillaries were rare in the young group and increased and occurred as collagen fibre bands and bundles around the capillaries and large blood vessels of middle aged and old group dogs. The thin elastic fibres increased from surface towards the deeper parts of the subintima of young dogs. In the middle aged group dogs, elastic fibres increased and thickened. The elastic fibres of the old group increased more and concentrated on the walls of the blood vessels and at the peripheries of the capillaries.
Keywords: Dog synovial membrane; age-associated synovial changes; collagen fibres; elastic fibres; capillaries-blood vessels; nerves